PERBEDAAN PENINGKATAN KEMAMPUAN KERJA ILMIAH SISWA MELALUI MODEL PEMBELAJARAN BERBASIS PROYEK PADA KONSEP PESAWAT SEDERHANA - Encep Andriana (JPsd (Jurnal Pendidikan Sekolah Dasar), 2015)
The increase differences of scientific inquiry skills of students through project based learning model pesawat concept. The ability of the scientific inquiry is an important element in the learning of science that must be mastered by the student . Scientific inquiry ability can be developed through learning activities that emphasize the process and challenging real experience . Project-based learning model is a model of learning that exposes students to real experience , problem solving , as well as students construct knowledge . This study aims to determine the increase in the ability of the scientific inquiry on the concept of pesawat sederhana of the impact of the implementation of project-based learning . This research method using a quasi-experimental design with randomized control group pretest - posttest design , which was held on 14,15 and June 16, 2012 , in SDN Karyawangi 2 as an experimental class and SDN Sukasari I as a control class . Data Networking capability of scientific inquiry using a multiple-choice test . Based on the results of hypothesis testing , the results showed that there are differences in the increase in the ability of the scientific work ( p = 0.00) between the students who get the project -based learning model ( N - Gain = 0.52 ) , with students getting conventional learning model ( N - Gain = 0.28 ) . Project-based learning model can be used as an alternative learning models that can be used to improve the ability of the scientific work on the concept of pesawat sederhana. Keywords : scientific inquiry , improved , pesawat sederhana